DIOSPENTENOLS A AND B, TWO NEW CYCLOPENTAPYRANS ISOLATED FROM ABANDONED MINE BACTERIUM STREPTOMYCES SP KMA-001 - Park, Jin-Soo; Cha, Jin Wook; Kim, Seong-Hwan; Oh, Dong-Chan; Kwon, Hak Cheol (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Two new cyclopentapyrans, diospentenols A and B were isolated from the Streptomyces sp. KMA-001 which was isolated from a heat-treated soil sample collected at the abandoned zinc mine. Spectroscopic analyses including extensive 2D NMR spectra, mass spectrometry, and chemical modification revealed structures of diospentenols consisted of 7,7a-dihydro-2H-cyclepenta[b]pyran-6-one core with a hydroxyl group and allyl side chain. This carbon skeleton is rare in natural products reported in the literature. Diosphenol, previously isolated from marine sponge and ascidian, is one of a few known natural products that possess this structural core. Each diospentenol was verified as a racemate using the modified Mosher method and chiral HPLC analysis.
Keywords: CYCLOPENTENONE DERIVATIVES; ABSOLUTE-CONFIGURATION; INHIBITORY-ACTIVITY; METABOLITES